Effects of water stress at different growth stages on comprehensive fruit quality and yield in different bunches of tomatoes in greenhouses - Hao, Shuxue; Cao, Hongxia; Wang, Hubing; Pan, Xiaoyan (International Journal of Agricultural and Biological Engineering, 2019)
The aim of this study was to investigate the effects of tomato quality and yield between different bunches and the differences between the two comprehensive evaluation methods on tomato quality ranking under water stress. Two degrees of water stress including mild water stress (W1) and moderate water stress (W2), and three growth stages that water stress applied including seedling stage (S1), flowering stage (S2) and fruit expanding stage (S3) were tested in this study. The yield and quality of different bunches of tomatoes under water stress during different growth stages were determined as responses, and the comprehensive fruit quality ranking and yield of the second and third bunches were evaluated. The results showed that water stress was important for the improvement of fruit quality, but fruit yield decreased during water stress. The yield of the third tomato bunch decreased from 11.69% (W1S1) to 30.60% (W2S2) compared to control (97.57 t/hm2), and the effects of mild water stress on fruit yield were minimal at the early growth stage. However, the fruit quality in terms of soluble sugar (SS), total soluble solids (TSS), vitamin C (VC), and firmness (F) improved under water stress compared to control. The combined effects of water stress and its application period significantly affected SS and TSS. Water stress significantly improved the content of SS and TSS in the later growth period compared to seedling and flowering stages. Meanwhile, there was a significant difference in tomato quality between the second and third bunches of fruit, especially in the content of SS, organic acid (OA) and lycopene (L). Principal Component Analysis (PCA) and Grey Relational Analysis (GRA) were used to evaluate comprehensive fruit quality, and the best treatment in terms of the fruit quality was W1S3 for both bunches. The rank-sum ratio (RSR) method was used to evaluate fruit quality and yield, the results showed that W1S3 ranked first based on PCA and W1S1 ranked first based on GRA. Water stress enhanced tomato quality but inevitably reduced its yield during each growth stage. The application of mild water stress during the fruit expanding stage (W1S3) was considered to be the best treatment to provide satisfactory fruit quality and yield based on RSR. Keywords: water stress, growth stages, tomato, comprehensive fruit quality, yield, greenhouse DOI: 10.25165/j.ijabe.20191203.4468 Citation: Hao S X, Cao H X, Wang H B, Pan X Y. Effects of water stress at different growth stages on comprehensive fruit quality and yield in different bunches of tomatoes in greenhouses. Int J Agric & Biol Eng, 2019; 12(3): 67–76.